Remote‐sensing‐derived fractures and shrub patterns to identify groundwater dependence. Issue 6 (3rd January 2018) - Guirado, E.; Alcaraz‐Segura, D.; Rigol‐Sánchez, J.P.; Gisbert, J.; Martínez‐Moreno, F.J.; Galindo‐Zaldívar, J.; González‐Castillo, L.; Cabello, J.
Abstract: The identification and location of groundwater‐dependent ecosystems are the first steps in protecting and managing them. Such identifications are challenging where the surface expressions of groundwater are not obvious. This work presents a remote‐sensing‐based approach to infer the groundwater dependence of semiarid shrubs from their association with fractures that facilitate root access to groundwater. As a case study, we used the Ziziphus lotus matorral in south‐east Spain, a priority conservation habitat in the European Union (Habitat 5220*, Directive 92/43/EEC) that is highly threatened by agricultural and urban sprawl. The approach combines object‐based image analysis of high‐resolution orthoimages to map Ziziphus individuals, geomorphometric analysis of a lidar‐derived terrain model to map bedrock fractures, and spatial statistics to assess the association between Ziziphus and fractures. Electrical resistivity tomography was used to validate the identified fractures, and the seasonal dynamics of the normalized difference vegetation index was used to prove that Z. lotus maintained higher greenness during the summer drought and was less coupled with precipitation than the nearby nonphreatophytic vegetation. A majority (61%) of the Ziziphus patches, particularly the smallest ones, occurred within 50 m of faults. This spatial association between phreatophyte shrubs and fractures contributes to the identification of groundwater‐dependent ecosystems. This approach offers several advantages because it is simple, low cost, and non‐destructive. In addition, the differentiation of shrubs into size classes provided insights into the long‐term environmental controls underlying the establishment of Ziziphus individuals. The evidence of groundwater dependence by Z. lotus in Habitat 5220* indicates the need for its urgent protection under the Water Framework Directive.